Synthesis of biodiesel by In-situ transesterification of Karanja oil - Sastry, SVAR; Murthy, CVR (Bangladesh Journal of Scientific and Industrial Research, 2015)
In the present study, biodiesel has been prepared from Karanja seeds which have been dried, dehulled and powdered. In-situ transesterification is done using the seed powder at a temperature of 50 °C. The molar ratio of methanol to oil (8:1, 7:1, 6:1, 5:1, 4:1, 3:1), KOH concentration (2.0 wt %, 1.5 wt %, 1.0 wt %, 0.5 wt %, 0.25 wt %) and time (60 min, 45 min, 30 min, 15 min and 10 min) were studied. In this method glycerol (which is obtained as a by-product in conventional method of biodiesel) is adsorbed onto the oilseeds. Hence the glycerol removal step is eliminated. To better evaluate the conversion of the vegetable oils into the respective methyl esters, the transesterification reactions were monitored by Thin Layer Chromatography (TLC). In this paper the feasibility of biodiesel formation is tested and is hence proven that biodiesel can be formed by this process. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22623 Bangladesh J. Sci. Ind. Res. 49(4), 211-218, 2014